(untitled) (Perner’s Contacts, 2013)
Supply chain security is a vital topic in today’s globalized world. Risks and threats to the supply chains affect business interests of involved stakeholders including customers. The paper discusses supply chain security dilemma with focus on supply chain security programs and initiatives as well as on mutual recognition programs within a business partnership.